A Comparative Evaluation of Antigen-Specific Sandwich Immunoassay and Indirect Immunofluorescence Assay (IIF) in Detecting Antineutrophil Cytoplasmic Antibodies: Are We Ready to Replace IIF with ELISA as the Primary Screening Method? - Deka, Sangeeta; Kalita, Deepjyoti; Shankar, Ravi; Rekha, U. Sasi; Sindhwani, Girish (Journal of Laboratory Physicians, 2021)
Background Antineutrophil cytoplasmic antibodies (ANCA) are important biomarkers in the diagnosis of ANCA-associated vasculitis, and indirect immunofluorescence (IIF) had been the method of choice for its detection from the very beginning. However, international consensus on ANCA testing (2017) advocates the use of high-quality immunoassays as the primary screening method. The purpose of this study was to evaluate the diagnostic performance of enzyme-linked immunosorbent assay (ELISA) compared to IIF in detecting ANCA.Methods One-hundred eighty-nine serum samples of suspected or known cases of systemic vasculitis were screened for ANCA by IIF and proteinase-3- and myeloperoxidase-ELISA. In IIF, positive results were further divided into cytoplasmic pattern of ANCA and perinuclear pattern of ANCA, depending upon the pattern of fluorescence. McNemar’s chi-squared test was applied to check the equality of proportions of positive results, and Kappa statistics was used to measure the agreement between the two methods. Diagnostic performance of ELISA was evaluated taking IIF as reference.Results IIF detected ANCA in 17.5% cases and ELISA detected it in 11.6% cases. A good agreement between the overall performance of ELISA and IIF was observed (K-value: 6.8, p-value: < 001). However, a significant difference in the proportion of positive results by the two methods was observed in McNemar’s test (two-sided p-value: 0.007). Taking IIF as standard, ELISA showed 60.6% sensitivity, 98.7% specificity, and predictive value of positive and negative results of 90.9 and 92.2%, respectively.Conclusion The new generation antigen-specific ELISAs had high specificity but the chances of missing cases in primary screening due to the low sensitivity and high false negativity (39.4%) need to be dealt with.
Keywords: ANCA; screening; PR3-ANCA; MPO-ANCA; ELISA; indirect immunofluorescence